The avizinhar in consolidation of the concept of extractivism in the acreana amazon, Bazil - Dourado da Silva, Rachel; Frejomil, Enrique Propin (Revista Geográfica de América Central., 2024)
The work consists of a historical-geographical reconstruction, using the popular orkers avizinhar in the consolidation of the orkers Extractivism in the Acrean Amazon. The methodology is based on bibliographic analysis, documents, fieldwork, interviews, public domain images. Extractivism developed throughout history throughout the world, with orkers biases: as na activity that has its action linked to na unprecedented extraction of elements of nature, extraction without due concern for orkers damage or the absence of such elements in the composition of the ecosystem. However, the orkers work seeks to orkers and conceptualize extractivism from the experience of the Amazon, in particular the Brazilian state of Acre that, despite complying with the etymology of the word, “withdrawal, collection of materials from nature”, transcends predatory extraction, and reverts into struggles for the conservation of nature and human lives that inhabit the forests. These actions were led by Chico Mendes in the mid-1980s through the union organization of forestry orkers initiated in the 1970s.